Middletown Baptist Church, New Jersey - Essick, John Inscore 1976- (Baptists in early North America series, 2022)
"Middletown Baptist Church in Monmouth County, New Jersey ("Old First Church" since 1963) was a key congregation in the development of Baptists in early America. It is the oldest Baptist congregation in New Jersey and one of the constituting churches of the Philadelphia Baptist Association in 1707. The records transcribed for Middletown Baptist Church include church meeting minutes, membership rolls, congregational correspondence, and personal letters which covers the period 1712 to 1811. The earliest years after the church's founding in 1688 are largely unknown due to discord and subsequent excision of records. Records for the years 1741 to 1785 are incomplete, but transcribed entries from "Elder Mott's Journal" provide a first-hand account of the church's life during that period. Of great interest here is the long ministry of Abel Morgan, Jr., an ordination controversy surrounding David Jones, the congregation's vote to expel members who did not support the Revolution, and the ultimate decision in 1836 to form two separate congregations: Middletown and Holmdel. Readers will also encounter lesser-known but compelling individuals like Lydia Mount, Elinor White, and James Grover. The records reveal a great deal about gender, race, and church conflict among the Baptists of New Jersey. It is also noteworthy that Middletown was in correspondence with congregations as far away as Kentucky. The volume concludes with a collection of fascinating appendices and a comprehensive index."